PERAN INDONESIA DALAM PENYELESAIAN SENGKETA LAUT NATUNA - Azzahra, Salsabila (LPPM Universitas Bina Bangsa, 2025)
The Natuna Sea is located in the Riau Province of Indonesia which is in the middle of the South China Sea or at the border point of the China Sea and Indonesia. The Natuna Sea is a strategic area in terms of economy, natural resources, and security. This has led to complex disputes involving various national and international interests. This article discusses how Indonesia's role in resolving the Natuna Sea dispute involving various countries. The research method used is a juridical-normative approach with literature studies related to the title to be discussed. The type of data used in this research is secondary data through laws and regulations and legal materials related to the problems to be studied. The result of this research is that China's claim to the Natuna Sea has no legality and validity or known as the “nine dash line”. Therefore, Indonesia must continue this dispute to the International Court of Justice so that China complies with applicable legal provisions and Indonesia can maintain territorial sovereignty in Natuna so that regional stability is maintained and protect the sovereign rights of every country over its legal sea area.